2021
DOI: 10.3847/2041-8213/ac242b
|View full text |Cite
|
Sign up to set email alerts
|

Chronicling the Host Galaxy Properties of the Remarkable Repeating FRB 20201124A

Abstract: We present the Australian Square Kilometre Array Pathfinder localization and follow-up observations of the host galaxy of the repeating fast radio burst (FRB) source, FRB 20201124A, the fifth such extragalactic repeating FRB with an identified host. From spectroscopic observations using the 6.5 m MMT Observatory, we derive a redshift z = 0.0979 ± 0.0001, a star formation rate inferred from Hα emission SFR(Hα) ≈ 2.1 M ⊙ yr−1, and a gas-phase metallicity of 12+log(O/H) ≈ 9.0. By jointly modeli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 123 publications
7
55
0
Order By: Relevance
“…The position of FRB 20201124A reported here is in agreement (within 2-σ) of the original EVN localisation reported in Marcote et al (2021) (which was determined using only the burst data from Epoch 1). Our position for FRB 20201124A is also in agreement with the independent measurements of the VLA (Ravi et al 2021), the Australian Square Kilometre Array Pathfinder (ASKAP) (Fong et al 2021), and the upgraded Giant Meterwave Radio Telescope (uGMRT; if one includes the estimated systematic errors they discuss; Wharton et al 2021a). These studies are approximately 3 orders of magnitude less precise than the localisation presented here (a comparison is shown in Figure 2).…”
Section: Localisationsupporting
confidence: 86%
See 1 more Smart Citation
“…The position of FRB 20201124A reported here is in agreement (within 2-σ) of the original EVN localisation reported in Marcote et al (2021) (which was determined using only the burst data from Epoch 1). Our position for FRB 20201124A is also in agreement with the independent measurements of the VLA (Ravi et al 2021), the Australian Square Kilometre Array Pathfinder (ASKAP) (Fong et al 2021), and the upgraded Giant Meterwave Radio Telescope (uGMRT; if one includes the estimated systematic errors they discuss; Wharton et al 2021a). These studies are approximately 3 orders of magnitude less precise than the localisation presented here (a comparison is shown in Figure 2).…”
Section: Localisationsupporting
confidence: 86%
“…The host galaxy of FRB 20201124A, SDSS J050803.48+260338.0 or hereafter J0508+2603 (Day et al 2021) is a massive, star-forming galaxy (Ravi et al 2021;Fong et al 2021) at a redshift of z = 0.098 (Kilpatrick et al 2021). The VLA (D-configuration; Ricci et al 2021) detected unresolved compact persistent emission at 3 GHz and 9 GHz, in addition to the uGMRT (Wharton et al 2021b) detection of unresolved persistent emission at 600 MHz.…”
Section: The Local Environment Of Frb 20201124amentioning
confidence: 99%
“…Another active repeater FRB 20201124A (Lanman et al 2021;Kumar et al 2021;Nimmo et al 2021;Hilmarsson et al 2021) is found in a Milky-Way-sized, metal-rich, barred-spiral host galaxy at z = 0.098 (Xu et al 2021;Fong et al 2021;Ravi et al 2021;Piro et al 2021). This repeater indicates a significant, irregular, variation of the Faraday rotation over 36 days.…”
Section: Introductionmentioning
confidence: 92%
“…This places a strong upper limit on the persistent source luminosity of 𝜈𝐿 𝜈 7.6 × 10 35 erg s −1 at 1.6 GHz, which is three orders of magnitude lower than that of FRB 20121102A. Recently, the CHIME/FRB collaboration announced heightened activity in the repeating FRB 20201124A (Chime/FRB Collaboration 2021), which was localised to a host galaxy at a redshift of 𝑧 = 0.0979 ± 0.0001 (Fong et al 2021). Persistent radio emission was detected by the upgraded Giant Metrewave Radio Telescope (uGMRT) (Wharton et al 2021) and the Karl G. Jansky Very Large Array (JVLA) (Ricci et al 2021) on angular scales of a few arcseconds, but resolved out to scales of ∼ 0.1 arcseconds with the European VLBI Network (Marcote et al 2021).…”
Section: Introductionmentioning
confidence: 98%